Characteristics of Patients With Community‐Acquired Pressure Injuries - Midori Nagano; Yoshiko Kubo; Akiko Egawa; Masayo Kobayashi; Masami Sato (Nursing Open)
ABSTRACT Aim (1) To classify patients with community‐acquired pressure injury (CAPI) according to the risk factors of PI and to assess validity of the classified groups. (2) To clarify characteristics of each group for CAPI prevention and care. Design This study is designed to classify CAPI patients into clusters based on a retrospective study of medical records, followed by cluster analysis and description of each cluster's characteristics. Methods Risk factors and status of CAPI, as well as discharge destination, were investigated based on 1 year's worth of medical records of patients with CAPI on hospital admission during 2018–2019. After calculating descriptive statistics, cluster analysis was conducted by Ward's method of Euclidean distance referring to risk factors of PI. Lastly, each of the defined clusters underwent multiple comparisons. Results From 324 patients with CAPI, 272 patients were selected as the study subjects, due to availability of sufficient information regarding risk factors of PI. After classification into three groups, data were interpreted by Euclidean distance and comparison between ‘attribute and risk factors of PI’ and ‘PI and destinations after discharge’. Patient or Public Contribution Patients with CAPI were classified into three clusters and validity of the classification was assessed. Patients who had ‘maintained ADL’, as well as cognitive status, were expected to be capable of self‐care and self‐management. Patients with ‘low ADL’ were characterised by insufficient self‐care or home care resulting in having CAPI and would require aged care service. Patients who were at ‘very high risk’ of having PI were characterised by incurring significant burden on caregivers and need of medical services that prospects terminal care.